THE EFFECT OF CONCEPT SENTENCE MODEL ON STUDENTS’ WRITING RECOUNT TEXT ABILITY ( at the Eighth Grade of SMP Negeri 3 Satu Atap Sosorgadong in 2020/2021 Academic Year) - sintia sihotang (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract : The aim of this research are to know: 1) the application of concept sentence model on teaching writing Recount Text ability, 2) the students writing recount text ability before and after using concept sentence model, 3) Whether there is any significant effect of concept sentence model on teaching writing recount text ability at the Eighth Grade Students of SMP Negeri 3 Satu Atap Sosorgadong. This research uses experimental method with pre-experimental design by using one-group pretest and posttest design. The populations of this research are all of the VIIIA grade students’ of SMP Negeri 3 Satu Atap Sosorgadong which consist of 71 students. Sample were VIII A which consist of 22 students which taken by purposive sampling. In collecting the data the researcher uses observation sheet and test as a composition test. The result of this research: 1) the application of concept sentence model was 3.8, it is categorized “Very Good”. 2) The mean score of the students’ writing recount text ability was 45 and it was categorized “fail”. Meanwhile, after using complete sentence model is 81, it is categorized “good”. The result of data analysis shows that ttest is higher than ttable (ttest 17.74> ttable 2.08). So, the hypothesis is accepted. It means that, there is any significant effect of concept sentence model on students’ writing recount text ability at the VIII A grade students of SMP N 3 Satu Atap Sosorgadong. Keywords: Concept Sentence Model, Writing Recount Text Ability Abstrak : Tujuan penelitian ini adalah untuk mengetahui: 1) Penggunaan dari concept sentence model terhadap kemampuan siswa menulis, 2) kemampuan siswa menulis sebelum dan setelah menggunakan concept sentence model, 3) Apakah ada pengaruh yang signifikan dari concept sentence model terhadap kemampuan siswa menulis di kelas delapan SMP Negeri 3 Satu Atap Sosorgadong. Penelitian ini menggunakan metode eksperimental. Populasi dari penelitian ini semua kelas delapan yang terdiri 71 siswa dan sampel terdiri dari 22 siswa dengan menggunaka porposive sampling. Dalam pengumpulan data, peneliti menggunakan lembar observasi. Instrument yang digunakan adalah observasi dan test adalah tes komposisi. Hasil penelitian ini adalah 1) penggunaan concept sentence model adalah 3.8, dikategorikan “sangat baik”. 2) Nilai rata-rata siswa sebelum menggunakan concept sentence model adalah 45, dikategorikan “gagal”. Sementara setelah menggunakan concept sentence model adalah 81, dikategorikan “baik”. 3) Hasil analisis data menunjukkan bahwa ttest lebih besar daripada ttable (ttest 17.74>ttable 2.08). Jadi, hipotesis diterima. Ini berarti ada pengaruh yang signifikan dari concept sentence model terhadap kemampuan siswa menulis di kelas delapan SMP Negeri 3 Satu Atap Sosorg/adong. Kata Kunci : Concept sentence Model, Writing, Recount Text